ChemInform Abstract: Synthesis, Crystal Structure, and Photocatalytical Properties of Ba3Ta5O14N. Issue 12 (March 2016) - Anke, B.; Bredow, T.; Soldat, J.; Wark, M.; Lerch, M.
Abstract: Phase‐pure Ba3 Ta V 5 O14 N is prepared via a sol‐gel based Pechini route by heating (200 °C) a 3:5 molar mixture of BaCl2 and TaCl5 in EtOH/citric acid/ethylene glycol prior to calcination at 400 °C.